Knee disorders in the general population and their relation to occupation. Issue 10 (22nd September 2003) - Baker, P; Reading, I; Cooper, C; Coggon, D
Abstract : Background: Hospital based studies of occupational risk factors for knee disorders are complicated by the possibility of selective referral to hospital of people whose work is made difficult by their symptoms. Aims: To explore the extent of such bias and to assess the association of meniscal injury with occupational activities. Methods: A questionnaire was mailed to a community sample of 2806 men aged 20–59 years in southern England. This asked about lifetime occupational and sporting activities, and any history of knee symptoms lasting 24 hours or longer. Rates of hospital referral were compared in symptomatic men according to their occupational activities. In a nested case-control investigation, the occupational activities of 67 men who reported meniscectomy were compared with those of 335 controls. Results: Among 1404 men who responded to the questionnaire, the lifetime prevalence of knee symptoms was 54%, and in 70% of cases the symptoms had started suddenly, usually while playing sport. Symptomatic men whose work entailed kneeling or squatting were more likely to be referred to an orthopaedic surgeon than the average (28% and 31% versus 24%), especially if they experienced locking of the knee (69% and 73% versus 43%). In the nested case-control study, meniscectomy was associated with playing soccer and work that involved regular kneeling or squatting. Conclusions: Results suggest that hospital referral for knee symptoms is influenced to some extent by patients' occupational activities. Playing soccer is confirmed as a strong risk factor for knee cartilage injury.